Nilai Religius Pada Kitab Puisi Balahindang Sakumpul Sapalimbayan Karya Iberamsyah Barbary - Irni Cahyani; Dana Aswadi; Akhmad HB (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
his study examines the religious value of the poem book Balahindang Sakumpul Sapalimbayan by Iberamsyah Barbary. The aims of this study are: (1) to describe religious values related to the human relationship with God, (2) to describe religious values related to human relationships with themselves. The approach used in this research is sociological. This type of research is library research. This research uses the descriptive analysis method. The data source of this research is the Book of Poetry Balahindang Sakumpul Sapalimbayan by Iberamsyah Barbary, published by the Nusantara Sastra Foundation in 2014. The data collection techniques in this study were documentation techniques and data analysis techniques. The results of the research obtained from the religious values in the poem book Balahindang Sakumpul Sapalimbayan by Iberamsyah Barbary include: (1) The religious values of human relations with God contained in the poetry book Balahindang Sakumpul Sapalimbayan by Iberamsyah Barbary, such as praying contained in the poems Assalamualaikum, Mamandir, Mambuka Lawang Heaven, and Bismillah. Religious values such as worship are found in the poems Assalamualaikum, Sakumpul Sapalimbayan, Read the Voice of God, Manuju Baitullah, Babaka Fasting, and Alhamdulillah. Religious values such as sincerity are found in Ikhlas poetry, and the religious value of repentance is found in Mamandir poetry. (2) The religious value of human relations with Himself is contained in the book of poetry Balahindang Sakumpul Sapalimbayan by Iberamsyah Barbary is like patience in the poem Babaka Puasa. The religious value of gratitude is the poem Alhamdulillah, the religious value of tawakal is found in the poems of Sakumpul Sapalimbayan and Mambuka Lawang Langit, the religious value of humility is located in the poems Read the Voice of God, Bismillah, and Ikhlas, the religious value of the view of life is found in the poetry of Manuju Baitullah, and the religious value of sincerity found in the poem Assalamualaikum.